Networks on chips technology and tools - Benini, Luca 1967- (Elsevier Morgan Kaufmann Publishers, 2006)
The design of today's semiconductor chips for various applications, such as telecommunications, poses various challenges due to the complexity of these systems. These highly complex systems-on-chips demand new approaches to connect and manage the communication between on-chip processing and storage components and networks on chips (NoCs) provide a powerful solution. This book is the first to provide a unified overview of NoC technology. It includes in-depth analysis of all the on-chip communication challenges, from physical wiring implementation up to software architecture, and a complete classification of their various Network-on-Chip approaches and solutions. * Leading-edge research from world-renowned experts in academia and industry with state-of-the-art technology implementations/trends * An integrated presentation not currently available in any other book * A thorough introduction to current design methodologies and chips designed with NoCs
Includes bibliographical references and index
Keywords: Systèmes sur une puce; Réseaux d'ordinateurs / Appareils et matériel; TECHNOLOGY & ENGINEERING / Electronics / Circuits / Integrated; TECHNOLOGY & ENGINEERING / Electronics / Circuits / General; Systems on a chip; Computer networks / Equipment and supplies; Networks on a chip / Congresses; Computer networks -- Equipment and supplies; Netzwerk; Integrierte Schaltung; Konferenzschrift